KENAKALAN REMAJA DI PERMUKIMAN KUMUH KAMPUNG MOROKREMBANGAN SURABAYA: the slum settlements - Sudiana, I Nengah (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2014)
Kampong Morokrembangan represent one of settlement which its environment condition concern. The drainage houses kampong Morokrembangan don’t fulfill the standard. This Matter is resulted from by slum and unhealthy house condition, wide mean of building 24 m2 dwelt by eight people and isn’t provided with by the hole of kitchen smoke, air ventilation, light ventilation and window. With the slum settlement condtion, this matter can influence the its society growth, especially children growth, because dwelling density and environmental cause the child become naughty. The research target is to know the adolescent mischief out the slum settlement, to know the parent role in educating child, to know the adolescent mischief storey level to its environment. This research hypothesis was tested using Chi-Square and data was obtained through questionnaire, interview and direct observation to hit the adolescent mischief and parent role about the condition of house physical in kampong Morokrembangan. The result indicates that the adolescent mischief because of the environmental condition of slum, causing the lack of meeting between child and parent. Beside that environmental of slum, causing its his difficult citizen to channel hobby.